Building Influencer Popularity Trends Through Beauty Content on Tiktok - Azzahra, Putri Salsabilla; Alianza, Ika; Imawan, Khaerudin (Publikasi Indonesia, 2025)
. TikTok is an effective platform for influencers to build popularity and increase interaction with audiences. This study aims to analyze Tasya Farasya's strategy in conveying beauty content on TikTok and its contribution to engagement and popularity. Using descriptive qualitative methods, data were collected through documentation, observation, and interviews. Data analysis was carried out using a qualitative content analysis approach. New media theory (Flew, Power, and Littlejohn) is used to understand the role of TikTok's digital interactivity, while Social Influence Theory (Kelman) explains Tasya's influence through three levels: compliance, identification, and internalization. The results of the study showed that Tasya Farasya leveraged TikTok's interactive features, such as comment replies, viral trends, and direct interactions to build engagement. The storytelling technique in product reviews and the